2017
DOI: 10.1111/jsr.12578
|View full text |Cite
|
Sign up to set email alerts
|

Memory encoding is impaired after multiple nights of partial sleep restriction

Abstract: SUMMARYSleep is important for normative cognitive functioning. A single night of total sleep deprivation can reduce the capacity to encode new memories. However, it is unclear how sleep restriction during several consecutive nights affects memory encoding. To explore this, we employed a parallelgroup design with 59 adolescents randomized into sleep-restricted (SR) and control groups. Both groups were afforded 9 h time in bed (TIB) for 2 baseline nights, followed by 5 consecutive nights of 5 h TIB for the SR gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 36 publications
(53 reference statements)
5
60
0
1
Order By: Relevance
“…General memory is also negatively impacted by sleep loss. Cousins et al, (Cousins et al, 2018) reported reduced recognition of previously encoded images after 5 consecutive nights or restricted sleep (5 hours) as compared to a control group and Chatburn et al, (2017) observed reduced veridical recognition and recall, and false memory recognition following both total and partial sleep deprivation (Chatburn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…General memory is also negatively impacted by sleep loss. Cousins et al, (Cousins et al, 2018) reported reduced recognition of previously encoded images after 5 consecutive nights or restricted sleep (5 hours) as compared to a control group and Chatburn et al, (2017) observed reduced veridical recognition and recall, and false memory recognition following both total and partial sleep deprivation (Chatburn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairment is the core symptom of dementia and can be considered a factor in the conversion from mild cognitive impairment to dementia. 42 Previous studies have indicated that acute sleep deprivation impairs memory encoding and consolidation 43 , 44 and that short sleep duration is associated with an increase in the risk of developing memory deficits. 45 Moreover, epidemiological studies 46 , 47 have found that long sleep duration is statistically significantly associated with memory deficits in both middle-aged adults and older participants, even after controlling for comorbidities, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic sleep restriction is associated with a wide range of physical and psychological deficits [1, 2] and has become increasingly prevalent in adolescents [3, 4]. In one study, less than 8% of high school students in the United States reported obtaining optimal sleep [5], while populations in East Asia consistently obtain below 6 hours on weekday nights [6–8], well below the 8–10 hours recommended by the National Sleep Foundation [9]. While the consequences of sleep deficits on development and academic achievement can be substantial, questions remain as to the amount of sleep restriction that leads to cognitive impairment, which cognitive faculties and underlying neurophysiology are worst affected, and the extent to which interventions such as daytime naps can alleviate these deficits.…”
Section: Introductionmentioning
confidence: 99%